2004
DOI: 10.1242/jcs.00940
|View full text |Cite
|
Sign up to set email alerts
|

The amount of neurofilaments aggregated in the cell body is controlled by their increased sensitivity to trypsin-like proteases

Abstract: Neurofilaments are synthesised and assembled in neuronal cell bodies, transported along axons and degraded at the synapse. However, in several pathological situations they aggregate in cell bodies or axons. To investigate their turnover when separated from their normal site of degradation, we used a previously described transgenic model characterised by perikaryal retention of neurofilaments, and compared the basic features of both neurofilament synthesis and degradation with that observed in normal mice. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Neuronal damage was assessed by NFL staining in the soma of cells in the gray matter. NFL aggregates in the neuronal soma during axonal injury (60) and NFL has been reported to aggregate in the neuronal body and axons in the spinal cord of rats with EAE (43). In this study, NFL aggregates were also found in spinal cord sections of mice with EAE.…”
Section: Discussionsupporting
confidence: 59%
“…Neuronal damage was assessed by NFL staining in the soma of cells in the gray matter. NFL aggregates in the neuronal soma during axonal injury (60) and NFL has been reported to aggregate in the neuronal body and axons in the spinal cord of rats with EAE (43). In this study, NFL aggregates were also found in spinal cord sections of mice with EAE.…”
Section: Discussionsupporting
confidence: 59%
“…Tubulin isotypes were identified using antibodies recognizing ␣-tubulin, ␤-tubulin, the neuronal specific ␤III-tubulin, ␥-tubulin (Sigma-Aldrich T9026, T4026, T8660), and polyglutamylated tubulin epitopes (GT335; generously provided by Dr. P. Denoulet, Paris, France). Experiments were performed in triplicate and membranes were incubated sequentially with each antibody (Fasani et al, 2004). Each reaction was revealed using a chemiluminescent protocol (ECL; GE Healthcare).…”
Section: Neurofilament Microtubule and Tubulin Isolationmentioning
confidence: 99%
“…The membrane was saturated overnight at 4°C with 10% milk powder diluted in TBS, washed three times 10 min with TBS, and incubated 1 h at 4°C with freshly purified phosphocellulose tubulin (3 mg/ml), and the excess of tubulin was removed by three washes with TBS at 4°C. Tubulin binding was revealed using classical Western blot protocol by anti-␤III-tubulin (Sigma-Aldrich) and a secondary antimouse peroxidase-labeled antibody (Dako) as previously described (Fasani et al, 2004). Soluble peptides corresponding to tubulin-binding sites (TBSs) and their reverse and scrambled sequences were synthesized by Millegen and added to MTs (S3 fraction from a MT preparation) to test their effect on MT polymerization.…”
Section: Neurofilament Microtubule and Tubulin Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofilament H expression was slightly reduced on day 2 after footshock (Figure 3C: t (10) = 2.422, p = 0.035), remained unchanged on day 28 but showed a trend towards a reduction on day 60 after footshock (Figure 3C: t (21) = 1.873, p = 0.075), while both MAP-2 and GFAP expression levels were not significantly altered at any of the three time points analyzed (Figure 3D, E, see Table 1 for summary of all tested proteins). Since neurofilaments are enzymatically degraded in synaptic structures [32], it is less likely that the subtle decrease in neurofilament H expression found here reflects synaptic loss, but more likely that it reflects persistent axonal degradation.…”
Section: Resultsmentioning
confidence: 81%